Semi Ideal on Supra Topological Space - Mayadah Khalil Ghaffar (Tikrit Journal of Pure Science)
In this paper we introduces the ideal on supra  topological space and we shall discuss the properties of this space. In this space we introduces  two operators ( )  and   . A generalized set has also been introduced in this space ( )  and  .